High‐resolution anorectal manometry: An expensive hobby or worth every penny?. Issue 8 (August 2017) - Basilisco, G.; Bharucha, A. E.
Abstract: Introduced approximately 10 years ago, high‐resolution manometry catheters have fostered interest in anorectal manometry. This review, which accompanies two articles in this issue of Neurogastroenterology and Motility, reviews the methods, clinical indications, utility, and pitfalls of anorectal manometry and revisits the American Gastroenterological Association (AGA) Medical Position Statement on Anorectal Testing Techniques, which was last published in 1999. High‐resolution manometry provides a refined assessment of the anorectal pressure profile, obviates the need for station pull‐through maneuvers, and minimizes movement artifacts. In selected cases, this refined assessment may be useful for identifying structural abnormalities or anal weakness. However, many manometry patterns that were previously regarded as abnormal are also observed in a majority of healthy patients, which substantially limits the utility of manometry for identifying defecatory disorders. It is our impression that most conclusions of the AGA medical position statement from 1999 remain valid today. High‐resolution techniques have not substantially affected the number of publications on or management of anorectal disorders. The ongoing efforts of an international working group to standardize techniques for anorectal manometry are welcome. Although high‐resolution manometry is more than an expensive hobby, improvements in catheter design and further research to rigorously define and evaluate these techniques are necessary to determine if they are worth every penny. Abstract : High‐resolution manometry (HRM) catheters provide better spatial resolution of anorectal pressures than standard (non‐HRM catheters) and minimize movement artifacts during manometry. However, with a few exceptions, HRM catheters have not increased the clinical utility of manometry to quantify anal weakness. By contrast to the esophagus, the number of publications related to anorectal manometry has not substantially increased after the introduction of HRM. Further studies are necessary, in particular to improve the currently limited utility of HRM for diagnosing defecatory disorders.